An efficiently biological nitrogen fixation of non-native Lotus tenuis justifies its key role in the flooding Pampas (Argentina) - Campestre, María Paula; Antonelli, Cristian Javier; Bailleres, Matias Andres; Gortari, Maximiliano; Maguire, Vanina Giselle; Ezquiaga, Juan Pedro; Taboada, Miguel Angel; Ruiz, Oscar Adolfo (Elsevier, 2025)
Forage production is a major challenge in the Salado River basin, Argentina (also denominated “Flooding Pampas”), the largest livestock raising area. The successful naturalization of the European legume Lotus tenuis (native from Mediterranean area) has been of productive and environmental relevance to the region. The main objective of this work was to quantify the efficiency of L. tenuis through its ability to fix nitrogen biologically and thus strengthening their strategic role in the region. The 15N natural abundance method was used to evaluate the Biological Nitrogen Fixation (BNF) of L. tenuis in soil plots. Non-leguminous weed species in the same plots were utilized as reference plants. Simultaneously, evaluations were carried out in the greenhouse and the relative reproducibility of the field experiments. The results showed that L. tenuis promotion was accompanied by an increase in forage quality improving the Crude Protein (CP) content and the Digestibility of Dry Matter (DDM). Moreover, its contribution to N inputs to the system through BNF in symbiosis with native rhizobia was about 80%, a highly relevant percentage for these constrained agroecosystems where the presence of native legumes is very scarce. In conclusion, this study supports the hypothesis that L. tenuis promotion plays a strategic role in ecosystem sustainability in the Salado River basin, especially in soil constrained areas. Together with previously published data, including information on ruminant management, the results obtained contribute to supporting the idea that the naturalized legume plays a strategic role in the sustainability of marginal agricultural soils.